PENGGUNAAN MEDIA PHET SIMULATION UNTUK MENENTUKAN WAKTU PARUH SUATU ATOM - MASFARATNA MASFARATNA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Physics quantum is a science that discusses object with very size _ small and not could seen with invisible . Physics quantum study that studies about behavior Theory as well as the energy that exists at the level molecular , atomic , nuclear as well as level microscopic . So that Relevant media is needed for teach Theory process decay Radioactive to participant educate in accordance with curriculum independent with approach scientific . Wrong one medium that is relevant to with Theory this that is Phet Simulation . Destination study this is for determine the relationship of the original nucleus and the number of remaining nuclei in the process decay so that could determined level decay in isotopes 14 C to 14 N and the isotope 238 U becomes 238 Pb at time 1st half , time 2nd half and time 3rd half . As well as for knowing level accuracy experiments carried out with use PhET virtual laboratory Simulation . As for method used _ in study this is method experiment that is with To do practice with sub menu “ Level Decay